Strategic Performance measurement system, Organisational capabilities and competatitive advantage - Rapiah Mohamed,; Wee Shu Hui,; Ibrahim Kamal Abdul Rahman,; Rozainun Ab Aziz, (2010)
This study examines organisational capabilities as a potential mediator in the link between SPMS use and organisational competitive advantage. The data was collected using a mail survey to top management of listed companies in Malaysia. The results show that SPMS makes a significant contribution with organisational competitive advantage and capabilities. However, diagnostic use is not significantly associated with organisational capabilities. The findings contribute to the body of knowledge by showing the role of SPMS from the perspective of the resource-based view theory and levers of control framework. The findings acknowledge that SPMS can be an indirect source for competitive advantage through its ability to enhance organisational capabilities.